Great Scientists: Guglielmo Marconi ( A Life Story) - Joseph, Mary (Sterling Publishers Private Ltd, 2012)
This inspiring series on great scientists has been specially planned for children. Young readers will find that science is fascinating and that it has made the world a far better place to live in.
Keywords: Juvenile Non-Fiction / Biography - Guglielmo Marconi